Visual Basic 2005 Recipes: A Problem-Solution Approach - Herman, Todd (Apress, 2013)
This book will not teach you everything you need know about developing VB .NET applications in Visual Studio 2005, but it will be invaluable as a stepping stone. Use the recipes as you need them, to help move your development projects along or to give you a starting point for your own experimentation